2017
DOI: 10.2196/humanfactors.7161
|View full text |Cite
|
Sign up to set email alerts
|

Fall Prevention Self-Assessments Via Mobile 3D Visualization Technologies: Community Dwelling Older Adults’ Perceptions of Opportunities and Challenges

Abstract: BackgroundIn the field of occupational therapy, the assistive equipment provision process (AEPP) is a prominent preventive strategy used to promote independent living and to identify and alleviate fall risk factors via the provision of assistive equipment within the home environment. Current practice involves the use of paper-based forms that include 2D measurement guidance diagrams that aim to communicate the precise points and dimensions that must be measured in order to make AEPP assessments. There are, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 73 publications
0
35
0
4
Order By: Relevance
“…Following review of 67 full-text papers, 14 studies met the inclusion criteria. These 14 studies were reported in 16 articles as presented in Table 1 (Atwal et al, 2013 andMoney et al, 2011 described the same study, as did Hamm et al, 2017a and2017b). Figure 1 shows the PRISMA chart summarising the search and study selection process.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following review of 67 full-text papers, 14 studies met the inclusion criteria. These 14 studies were reported in 16 articles as presented in Table 1 (Atwal et al, 2013 andMoney et al, 2011 described the same study, as did Hamm et al, 2017a and2017b). Figure 1 shows the PRISMA chart summarising the search and study selection process.…”
Section: Search Resultsmentioning
confidence: 99%
“…The 3D-MAP program is a mobile application that draws on three-dimensional visualisation technology and aims to facilitate services users to record measurements within the home as part of the assistive equipment provision process (Hamm et al, 2017a(Hamm et al, , 2017b). Hamm and colleagues conducted surveys and focus groups with healthy adults (aged over 50 years) (Hamm et al, 2017a) and Evaluate the feasibility of using an interactive 3D home visualisation software as a tool to aid occupational therapists in carrying out pre-discharge home visits and explore the attitudes of occupational therapists toward technology in general Most therapists were not using technology with clients within their practice but recognised the need to do so Potential benefits of software for discharge planning identified: reduce cost when transporting client difficult, when the home is some distance away and when the client cannot take part in the visit Concern that software would be used to replace home visits Atwal et al (2014), UK Qualitative: think-aloud data captured while using technology and subsequent semi-structured interviews with occupational therapists Female: 57%; age, mean (SD): not reported; N ¼ 7 Occupational therapists within the UK health sector familiar with using desktop computers and typical applications…”
Section: Results Of Studiesmentioning
confidence: 99%
“…This review found a developing interest toward assessing patient-environment fit in the technology-based home assessment tools (Hamm et al, 2017(Hamm et al, , 2019Hoffmann & Russell, 2008). However, the consideration of patient fit was only limited to measuring popliteal height in one tool, and in another, video observations of resident's movement around the house.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, some tools require participants to measure popliteal height (the height from underside of feet to underside of knee) and furniture dimensions. Two assessments that required such tasks were conducted by professionals with assistance from the older adults (Hoffmann & Russell, 2008;Spiliotopoulou et al, 2018) and one was used by the individual alone (Hamm et al, 2017).…”
Section: Built Environment Assessment Componentsmentioning
confidence: 99%
“…For those who actually perform the data analysis tasks, many ambiguous areas remain, such as the crossover among older people between fallers and non-fallers, as well as the different classification cut points. Therefore, a perception of the feasibility, acceptability, and availability of new tools and techniques in clinical practice [29,30] via data visualization is essential. This perception is far more critical than the usage of community services in obtaining an initial judgment of subhealth.…”
Section: Introductionmentioning
confidence: 99%